Human T2R38 Bitter Taste Receptor Expression in Resting and Activated Lymphocytes - Tran, Hoai T. T.; Herz, Corinna; Ruf, Patrick; Stetter, Rebecca; Lamy, Evelyn (Frontiers in Immunology, 2018)
The human G-protein-coupled bitter taste receptor T2R38 has recently been demonstrated to be expressed on peripheral blood neutrophils, monocytes and lymphocytes. To further define a potential contribution of the T2R38 receptor in adaptive immune response, the objective of this study was to analyze its expression in resting and activated lymphocytes and T cell subpopulations. Freshly isolated PBMC from healthy donors were used for expression analysis by flow cytometry. Quantum™ MESF beads were applied for quantification in absolute fluorescence units. Activation methods of T cells were anti-CD3/CD28, phytohaemagglutinin (PHA) or phorbol 12-myristate 13-acetate (PMA) together with ionomycin. Lymphocytes from young donors expressed higher levels of T2R38 compared to the elderly. CD3+ T cells expressed higher levels that CD19+ B cells. Receptor expression followed T cell activation with an upregulation within 24h and a peak at 72h. Higher levels of T2R38 were produced in lymphocytes by stimulation with anti-CD3/CD28 compared to PHA or PMA/ionomycin. Both subpopulations of CD4+ as well as CD8+ T cells were found to express the T2R38 receptor; this was higher in CD4+ than CD8+ cells; the amount of T2R38 in central and effector memory cells was higher as compared to naïve cells, although this was not statistically significant for CD8+ cells without prior activation by anti-CD3/CD28. Upon treatment of PBMC with the natural T2R38 agonist goitrin Calcium flux was activated in the lymphocyte population with functional T2R38 receptor at >20 µM which was completely blocked by phospholipase Cβ-2 inhibitor U73211. Further, goitrin selectively inhibited TNF-alpha secretion in PBMC with functional T2R38. This quantitative analysis of T2R38 expression in distinct PBMC subsets may provide a basis for understanding the significance of bitter compounds in immune modulation. Whether these findings can have implications for the treatment of inflammatory and immunologic disorders by bitter tasting pharmaceuticals or foods needs further investigation.